A strategic roadmap for ASEAN to develop hydrogen energy: Economic prospects and carbon emission reduction. (8th April 2023) - Li, Yanfei; Suryadi, Beni; Yan, Jianjun; Feng, Junyi; Bhaskoro, Adhityo Gilang; Suwanto,
Abstract: The progress of hydrogen energy in terms of technologies and supply chains is appealing to member countries of the Association of Southeast Asian Nations (ASEAN). Countries with the advantages of fossil fuel resources and existing infrastructure can export grey hydrogen energy until 2025. This could help expand hydrogen-related infrastructure and form a certain level of economies of scale to prepare for the next phase of development of blue and green hydrogen energy. From 2026 to 2030, ASEAN could shift to blue hydrogen energy exports with the help of carbon capture, utilization, and storage. However, the domestic applications of hydrogen energy will remain economically uncompetitive in most ASEAN countries. After 2030, as the levelized costs of electricity for renewables decline and the share of renewable energy power increases, the cost of hydrogen energy production from surplus electricity could become even lower. Consequently, green hydrogen energy will dominate domestic downstream energy applications and exports to overseas markets. Highlights: By 2030, domestic applications of hydrogen energy in ASEAN remain uncompetitive. Export of grey hydrogen is marginally competitive with existing infrastructure. By 2030, as infrastructure scales up, ASEAN can export blue hydrogen using CCS. After 2030, green hydrogen is competitive for domestic applications and exports. Strategies for phased developments of hydrogen energy in ASEAN are thus advised.